DIAGNOSIS OF OVARIAN REMNANT SYNDROME AND LAPAROSCOPIC EXCISION IN BITCHES - GULAWANE, S U; CHARIAR, V M; KHARE, Y B (The Indian Journal of Animal Reproduction, 2011)
Ten spayed bitches with history of pro estrual bleeding, vulval swelling, attractiveness to male were diagnosed as cases of ovarian remnant syndrome based on vaginal cytology and serum progesterone assay. Diagnostic laparoscopy was performed in metestrus and the ovarian remnants were removed by laparoscopic dissection. None of the bitches showed any surgical complications. Only in one bitch vaginal bleeding continued which was diagnosed as polyps in the vagina on vaginoscopy. It was concluded that the diagnosis of ovarian remnant syndrome can be done by serial vaginal cytology ar:id serum progesterone assay. Confirmation and further removal of ovarian remnant can be performed by laparoscopy.